Laminoplasty provides better functional outcomes than laminectomy in the management of cervical stenosis myelopathy: a systematic review - Putu Kermawan; I Ketut Siki Kawiyana; I Gusti Ngurah Wien Aryana; I Gusti Lanang Ngurah Agung Artha Wiguna; I Gede Eka Wiratnaya; I Ketut Suyasa (Intisari Sains Medis, 2021)
Background: Increasing the life expectancy of an individual will be accompanied by the emergence of various degenerative diseases such as cervical stenosis myelopathy (CSM). CSM is characterized by the presence of signs and symptoms of spinal cord compression associated with narrowing the spinal canal dimensions. Decompression can be achieved by conventional methods such as laminectomy or a lamina reshaping procedure known as a laminoplasty. This study reports recent evidence regarding laminectomy and laminoplasty procedures in managing CSM in terms of functional outcomes.Methods: A systematic search was conducted on the PUBMED database to identify and find studies comparing laminoplasty and laminectomy procedures. Inclusion criteria included patients older than 65 years diagnosed with cervical myelopathy, including CSM and/or ossified posterior longitudinal ligament (OPLL). Randomized controlled studies and prospective and retrospective cohorts were included in this study, while case series and case reports were excluded. The comparison of effectiveness is based on the results of measuring functional outcomes using the Japanese Orthopedic Association (JOA) score, neck disability index (NDI), and the visual analogue scale (VAS) for pain assessment.Results: A thorough search through the PUBMED database yielded 156 citations. Scanning titles and abstracts from studies that met the inclusion and exclusion criteria resulted in 14 articles. All articles have a retrospective cohort design. In total, there were 187 patients in the laminoplasty group and 161 patients in the laminectomy group. There was no significant difference between laminoplasty and laminectomy when viewed from the JOA score in weighted mean difference (WMD) (WMD 0.28; 95% Confidence Interval [CI]:-0.34-0.91) and VAS score (WMD 0.06; 95% CI: -1.13-1.02). However, laminoplasty was shown to have a better NDI score (WMD 3.32; 95% CI: -6.50-0.14).Conclusion: Laminoplasty is superior to laminectomy for managing cervical myelopathic stenosis in terms of NDI score.